CRITERIA FOR PROVIDING MEMBERSHIP PRINCIPLES FOR TYPES OF EDUCATIONAL ACTIVITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses in detail the general issues and peculiarities of the education of students in continuing education as harmoniously developed people.